ASSESSMENT OF TRANSPARENCY OF AUDIT REPORTS BASED ON PRESENTATION OF KEY AUDIT MATTERS – THE CASES OF BOSNIA AND HERZEGOVINA AND CROATIA (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2021)
Purpose: One of the ways to enhance transparency and usefulness of audit reports is to include information on key audit matters (KAMs). In this paper, based on the presented KAMs, we investigate transparency of audit reports of listed companies in Bosnia and Herzegovina and in Croatia.Methodology: For the purposes of this research, we collected and systematised data from published audit reports and then analysed them by means of descriptive statistical methods.Results: The research results show that in Croatia only a few audit reports lack a section on KAMs and there is no difference between the audit reports issued by the Big Four and the reports of other audit firms. In Bosnia and Herzegovina, most audit reports do not include a section on KAMs, but, unlike the Big Four, who disclose at least one KAM, other audit firms generally do not present any. Additionally, the research results show differences in the number of communicated KAMs between the audit reports prepared by the Big Four in Croatia and their reports for Bosnia and Herzegovina. There are also differences in the type of KAMs used in the two observed countries.Conclusion: Having analysed the situation in the two developing countries, we obtained different results. The discrepancies mainly stem from the varying degrees of transparency of the audit profession in each country.